Penerapan Konseling Behavioral dengan Teknik Penokohan (Modelling) untuk Meningkatkan Motivasi Belajar Siswa Kelas VII A SMPK 2 Harapan Tahun Pelajaran 2019/2020 - I Dewa Ayu Eka Purba Dharma Tari; Kadek Suhardita; I Putu Karpika; I Ketut Sapta; Ni Luh Rosita Diantari (Universitas Kanjuruhan Malang, 2020)
The purpose of this study was to determine the effectiveness of Behavioral Counseling with modeling techniques to increase learning motivation of class VII A SMPK 2 Harapan students in the 2019/2020 academic year. This research is a classroom action research conducted in two cycles. Research subjects in this study were 36 students. Through the observation questionnaire assessment conducted there were 5 students who have low learning motivation. The results of this study indicate that from 19.14% to 35.71% with an initial data score of 43.8%, an increase of 30.34% to 57% in the low category. Furthermore, the results of the second cycle (II) action, it is clear that there is an increase in the learning motivation of class VII A students of SMPK 2 Harapan for the 2019/2020 academic year from 22.03% to 36.36% with an initial data score of 57%, an increase of 29.95%. to 74% in the high category. This proves that behavioral counseling with modeling techniques is effective for increasing learning motivation of grade VII A students of SMK 2 Harapan for the 2019/2020 academic year.